The Integrity of the Marinid kingdom’s administrative system - Jamsari, E.A.; Ashari, M.Z.A.H.; Sidek, R.S.M.; Nor, M.R.M. (Medwell Journals, 2012)
Being an Islamic kingdom in the medieval period, the Marinids (1215-1465M) is regarded as a good and strong one when it was able to rule the entire al-Maghrib during its days of glory. This paper aims to review the governance system of the Kingdom of Marinid which includes its administration and personnel recruitment. In addition, this paper seeks to identify the duty and role that each government departments played during the era of the Marinids. This study used the method of qualitative study which involves both historical study and content analysis methods. The finding showed that the long life span of the Marinids and its ruling power in al-Maghrib was due to the kingdom’s effective governance system which has clearly defined and documented authorities for all roles in each government departments.